Statistics for special q, t-kostka polynomials - Fishel, Susanna (Proceedings of the American Mathematical Society, 1995)
Kirillov and Reshetikhin introduced rigged configurations as a new way to calculate the entries of the Kostka matrix. Macdonald defined the two-parameter Kostka matrix whose entries generalize. We use rigged configurations and a formula of Stembridge to provide a combinatorial interpretation of in the case where is a partition with no more than two columns. In particular, we show that in this case, has nonnegative coefficients. © 1995 American Mathematical Society.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/082-420-581-698-924
Keywords: dept.mat

Canonical bases for the Brauer centralizer algebra - Fishel, Susanna; Grojnowski, I (Mathematical Research Letters, 1995)
Citation Key Alias: lens.org/069-225-958-557-87X tex.type: [object Object]
Keywords: dept.mat